Coherence in The Narrative Texts of Eastvaganza Story Writing Contest for Senior High-School Students - Mamduhan, Rifqi Hazmi; Fitriati, Sri Wuli; Sutopo, Djoko (Universitas Negeri Semarang, 2019)
This study analyzes narratives written by six students who joined a story writing contest. It is assumed that the students who joined in the writing contest had fair knowledge in writing, so the texts may achieve coherence. This study uses qualitative research in the form of discourse analysis. The focuses of the study are to investigate micro and macro level coherence, tense use, and the context of situation of the texts. This study uses the theories from Thornbury (2005), Ellis (1997), and Eggins (1994). This study is aimed to know the quality of coherent text in the students’ narrative. The findings of this study showed that constant theme patterns became the most frequent occurred in the narratives followed by zig-zag patterns and sentences which has no patterns. The sentences which have patterns might be logic in continuity. For the macro-level coherence, key word aspect became the most found in the narratives. The words represented the main characters in the stories. The macro-scripts showed that the narratives mostly use the script orientation-complication-resolution in arranging the paragraphs. The tense errors were found in almost all narratives. The findings showed three narratives had more errors than correct ones. The situational coherence showed that the fields in the texts were about heroes who had done something precious in their life. The tenors of the texts were same, namely between story writers and story readers. The modes of the texts were also the same. The texts are delivered by written media, so the texts did not have visual and aural distance between story writers and story readers. The goal of the texts is only for constructing experience.